Space, Body and Displacement Through Cuba and the Soviet Orbit in the Narratives of Anna Lidia Vega Serova (Ánima Fatua and Imperio Doméstico) and Maité Hernández-Lorenzo (Las Memorias Vacías de Solange Bañuelos); [Espacio, Cuerpo y Desplazamiento por Cuba y la Órbita Soviética en Las Narraciones de Anna Lidia Vega Serova (Ánima Fatua E Imperio Doméstico) y de Maité Hernández-Lorenzo (Las Memorias Vacías de Solange Bañuelos)] - Jeftanovic-Avdaloff, A (University Library System, University of Pittsburgh, 2023)
This essay explores the relationship between space and displacement in the narratives of two women writers: Anna Lidia Vega Serova and Maité Hernández-Lorenzo. Especially in the titles Ánima Fatua and Imperio doméstico by the first and Las memorias vacías de Soledad Bañuelos by the second. Both Cuban authors share a narrative that puts women’s bodies at the center and documents displacements through cities of the Soviet orbit –belonging to Russia and Poland– and then the body trapped or confined in Havana City during the so-called Special Period (1991- 1995). © 2023 Authors. All rights reserved.